European Investigation Order and the “Brussels” Bureaucracy - Kordík, Marek; Kurilovská, Lucia (Public Governance, Administration and Finances Law Review, 2018)
The contribution deals with the insight on the European investigation order, as a tool of mutual judicial assistance in criminal matters. With the purpose to show that the criticised, so called Brussels bureaucracy very often just reacts on the propositions of the member states. A good example of this is given in the presented article. It shows the result of a conducted CEPOL survey and connects it with the short presentation of this tool.